Epidemiological profile of 39 cases of microcephaly caused by congenital infections diagnosed in the state of Rio Grande do Sul between 2015-2017 - Herber, Silvani (2020)
Introduction: Microcephaly is a clinical finding that can arise from congenital anomalies or emerge after childbirth. Maternal infections acquired during pregnancy can result in characteristic brain damage in the newborn (NB), which may be visible even in the fetal stage. To describe the epidemiological profile of newborns with reported microcephaly and diagnosed with congenital infections in the state of Rio Grande do Sul between 2015 and 2017. Methods: A cross-sectional study was carried out on data collected from the Public Health Event Registry as well as from medical records. The investigation included serologies for toxoplasmosis and rubella; polymerase chain reaction (PCR) for Zika virus (ZIKV) in the blood and cytomegalovirus in the urine; non-treponemal tests for syphilis; and brain imaging tests. Results: Of the 257 reported cases of microcephaly, 39 were diagnosed with congenital infections. Severe microcephaly was identified in 13 patients (33.3%) and 51.3% of the cases showed alterations in brain imaging tests. In relation to the diagnosis of congenital infections, three patients (7.7%) were diagnosed with ZIKV, nine (23.1%) with cytomegalovirus, nine (23.1%) with toxoplasmosis, and 18 (46.1%) with congenital syphilis. The three cases of ZIKV showed calcification in brain imaging tests, signs of arthrogryposis, excess occipital skin and irritability, characterizing the typical phenotype of ZIKV infection. Conclusions: Most cases of congenital infection had severe neurological lesions, particularly the cases of ZIKV, which can cause neurodevelopmental delays and sequelae in these infants throughout early childhood.